PENGARUH HEALING TOURISM TERHADAP JUMLAH KUNJUNGAN WISATAWAN DI DESTINASI EMBUNG TERPADU DESA WISATA DAYUN - Hayati, Maikel; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
In simple terms, Healing Tourism can be interpreted as a type of tourism that aims to provide a calming and restorative experience for tourists by traveling to visit tourist destinations that have Healing Tourism potential. The phenomenon that occurs is that even though the Dayun tourism village has the potential for Healing Tourism, the number of visits to the Dayun tourism village actually fluctuates. By knowing the most influencing Healing Tourism factors, it is hoped that Dayun tourism destinations can maximize the potential of these factors so that the number of tourist visits to Dayun tourism destinations no longer fluctuates. The purpose of this study is to see how much Healing Tourism has an influence on the increase in tourist visits in Dayun Tourism Village and which Healing Tourism factors have the greatest influence. The population is visitors to Dayun tourist destinations totaling 44,769 samples used in this study are 97 people. Healing Tourism has a significant effect on increasing tourist visits, the level of closeness is at a moderate level. Where the results of the correlation test obtained a probability number of 0.000 where this value is less than 0.05 (0.000 < 0.05) H0 is rejected and Ha is accepted, which means that there is a significant relationship between Healing Tourism and tourist visits, the correlation coefficient produced is 0.465. Keywords : Healing Tourism, tourism village